Uncovering the Impact of Yellow Cards on the Performance of the Liga 1 BRI Football Team for the 2023-2024 Season - Hidayat, Rodhi Rusdianto; Dwipa, Bhakti Saka; Adelia, Syarifa; Ledoh, Cartika Candra; Sirampun, Elsi; Nasruddin; Putra, I Putu Eka Wijaya; Ibrahim; Ansar CS; Kurdi; Putra, Miftah Fariz Prima; Sinaga, Evi; Larung, Ermelinda Yersin Putri; Kustiawan, Andri Arif; Muhammad, Junalia; Mandosir, Yohanis Manfred; Lewier, Meilani Paulina (Fair Play, 2025)
This study aims to examine the effect of yellow cards on the performance of football teams in Liga 1 BRI Indonesia season 2023-2024. The core issue raised is how yellow cards affect ball possession, goal scoring, and overall match results. The method used was a quantitative correlative research design, with data collected from 18 teams (9 provinces) over a full season (11 months). Analyses were conducted using Pearson correlation test, linear regression, and analysis of variance (ANOVA) to evaluate the impact of yellow cards in various match conditions. The results showed that yellow cards had a significant negative impact on possession (coefficient: -0.341, p<0.001) and goal scoring (coefficient: -0.017, p=0.003), especially in away matches and against stronger opponents, as well as when received by key players such as central midfielders or defenders. The conclusions of this study highlight the importance of yellow card risk management strategies and psychological resilience training for players, as well as the relevance of these findings in developing team competitive strategies. This research provides a new contribution to the literature on discipline in football and practical implications for football team management.